The relationship between eating habits and psychological stress levels with the incidence of gastritis in adolescents: An approach based on the DASS-42 scale - Saputri, Asmiana Ilyas; Zulfitrawati (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: One of the conditions frequently seen in hospitalized patients is gastritis, which is an inflammation of the stomach mucosa that can be either acute or chronic. High levels of stress and an improper diet are the main causes of gastritis. More research is required to determine the reasons linked to the occurrence of gastritis in adolescents, as the prevalence of the condition has dramatically grown in the Moncongloe Community Health Center operating area. Method: This study employs a cross-sectional design and a quantitative methodology. Using an accidental sampling technique, 58 respondents made up the sample. A questionnaire covering diet, stress measured by the Depression Anxiety Stress Scale (DASS-42), and the prevalence of gastritis was used to gather data. Data analysis was carried out using the chi-square test with a significance level of α = 0.05. Results: According to the study's findings, teenagers with gastritis were more likely to have poor eating habits (56.8%). While the association between diet and the incidence of gastritis was not statistically significant (p = 0.051), statistical testing revealed a significant relationship between stress levels and the condition (p = 0.042). Conclusion: Stress levels and the prevalence of gastritis in teenagers in the Moncongloe Community Health Center's service area are significantly correlated. Even though there is no statistically significant correlation between diet and gastritis, teenagers who suffer from gastritis are more likely to eat poorly. In order to lower the incidence of gastritis in teenagers, this study highlights the need of stress management and instruction on appropriate eating habits. Novelty/Originality of this article: This study highlights the importance of psychological factors, particularly stress, in the occurrence of gastritis in adolescents, which has rarely been the main focus in similar studies. In addition, the use of the Depression Anxiety Stress Scale (DASS-42) to measure stress in the context of adolescent gastritis provides a more quantitative approach than previous studies.